Corporate Social Responsibility (CSR) & Its Implementation towards Good Governance - Mr. Saurabh Jha**, Dr. Arvind Kumar Singh* (International Journal of Scientific Research and Management (IJSRM), 2017)
We are living in a world surrounded with numerous problems related to environment and society. CSR(Corporate Social Responsibility) is a means to sort out these problems to some extent because business isa part of society. Any contribution towards welfare of society is called as Corporate can no longer limitthem in using resources of society and they have to be socially responsible corporate citizens and must alsocontribute to the social good. Corporate Social Responsibility is now accepted as a means to achievesustainable development of an organization. In the present time, CSR has become a significant sector ofmodern corporate research theory and the growth of activities related to CSR in all over the world isremarkable. According to Company Act, 2013, those companies which are within the domain of section135 of Companies Act 2013 must spend 2% of their net profits towards CSR, in the fields as specified underschedule VII, which made Indian companies to consciously work towards CSR. This research paper is basedon the hypothesis, Compliance of provision relating to CSR under section 135 of the Companies Act 2013& Companies (Corporate Social Responsibility Policy) Rules, 2014, both in letter and spirit would providea way for Corporates, to achieve Corporate Sustainability, through promoting Good Governance to allstakeholders with in the society, in which they or their business activities are running.